Destruction of Bacillus cereus spores in a thick soy bean paste (doenjang) by continuous ohmic heating with five sequential electrodes. (July 2016) - Ryang, J.H.; Kim, N.H.; Lee, B.S.; Kim, C.T.; Rhee, M.S.
Abstract: This study selected spores from Bacillus cereus FSP‐2 strain (the isolate from a commercial doenjang processing line) as the test strain which showed significantly higher thermal resistance ( P < 0·05) than B. cereus reference strain (ATCC 27348). The spores in doenjang were subjected to ohmic heating (OH) at 95, 105, 115 and 125°C for 30, 60 or 90 s using a five sequential electrode system (electrical field: 26·7 V cm −1 ; alternating current frequency: 25 kHz). OH at 105°C for 30–90 s reduced the B. cereus spore count in doenjang samples to <4 log CFU g −1 . Since OH treatment at 115 and 125°C caused a perceivable colour change in the product (>1·5 National Bureau of Standards units), treatment at 105°C for 60 s was selected and applied on a large scale (500 kg of product). Reliable and reproducible destruction of B. cereus spores occurred; the reductions achieved (to < 4 log CFU g −1 ) met the Korean national standards. Scanning electron microscopy revealed microstructural alterations in the spores (shrinkage and a distorted outer spore coat). OH is an effective method for destroying B. cereus spores to ensure the microbiological quality and safety of a thick, highly viscous sauce. Significance and Impact of the Study: This study shows that an ohmic heating (OH) using a five sequential electrode system can effectively destroy highly heat‐resistant Bacillus cereus spores which have been frequently found in a commercial doenjang processing line without perceivable quality change in the product. In addition, it may demonstrate high potential of the unique OH system used in this study that will further contribute to ensure microbiological quality and safety of crude sauces containing high levels of electrolyte other than doenjang as well. Abstract : Significance and Impact of the Study: This study shows that an ohmic heating (OH) using a five sequential electrode system can effectively destroy highly heat‐resistant Bacillus cereus spores which have been frequently found in a commercial doenjang processing line without perceivable quality change in the product. In addition, it may demonstrate high potential of the unique OH system used in this study that will further contribute to ensure microbiological quality and safety of crude sauces containing high levels of electrolyte other than doenjang as well.